2017
DOI: 10.1515/ppb-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Empathy gap – what do we know about empathizing with others′ pain?

Abstract: Empathy of pain as a multi-dimensional process includes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…In the shared condition, pain increased the perceived bonding by promoting empathy, which is consistent with previous literature (Lamm, Batson, & Decety, 2007). Witnessing others’ pain can trigger empathic responses (Abu-Akel, Palgi, Klein, Decety, & Shamey-Tsoory, 2015; Dopierała, Siuda, & Boski, 2017). Studies have also shown that even though there are qualitative differences between experiencing pain firsthand and observing others’ pain, there is an overlap in the neurological mechanisms of the two processes to some extent (Lamm et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the shared condition, pain increased the perceived bonding by promoting empathy, which is consistent with previous literature (Lamm, Batson, & Decety, 2007). Witnessing others’ pain can trigger empathic responses (Abu-Akel, Palgi, Klein, Decety, & Shamey-Tsoory, 2015; Dopierała, Siuda, & Boski, 2017). Studies have also shown that even though there are qualitative differences between experiencing pain firsthand and observing others’ pain, there is an overlap in the neurological mechanisms of the two processes to some extent (Lamm et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…, 2013 ). Intriguingly, the simulation of others’ pain the network produces is not equal in all circumstances but varies as a function of social factors such as perceived similarity between oneself and the victim ( Dopierała et al. , 2017 ; Han, 2018 ).…”
Section: Introductionmentioning
confidence: 99%